Analisis Karya Ilmiah Makalah Siswa Kelas XI SMA Negeri 14 Padang - Eva Fitrianti; Dwi Muthia Chan; Melawati (Kilau Publishing, 2024)
Writing is the highest level of language skill. Writing is a form of interaction that conveys one’s feelings, ideas, and thought to other through written form. In the merdeka curriculum, one of the materials studied for writing skills at the 11th grade high school level is scientific paper writing. Student’s scientific paper writing skills still contain many errors. In this regard, the purpose of this research is to decribe and analyze the scientific paper writing of 11th grade students at SMA Negeri 14 Padang. This research is qualitive study using a descriptive method, which describes each word and sentence. The research instrument used was the researcher herself, with supporting instruments being an interview guide. Data collection techniques used interviews and documentation. Data analysis techniques used data reduction, data presentation, and drawing conclusions. The results of the study showed that students were still unable to write papers properly and correctly because there were still many errors. Students still have difficulty in making a table of contents and problem formulation. Students still do not understand how to cite other people's opinions, students only quote the entire results of other people's research. Students also have difficulty in the closing section of the paper, namely the section on writing suggestions. The linguistic elements in the paper, the paper does not use the pronouns I or we, it uses standard words, uses straightforward language and sentences with denotative meaning.